Comparison of PREDICTS atherosclerosis biomarker changes after initiation of new treatments in patients with SLE. Issue 1 (27th June 2019) - McMahon, Maureen; Skaggs, Brian; Grossman, Jennifer; Wong, Weng Kee; Sahakian, Lori; Chen, Weiling; Hahn, Bevra
Abstract : Objective: Patients with SLE have an increased risk of atherosclerosis (ATH) that is not adequately explained by traditional risk factors. We previously described the Predictors of Risk for Elevated Flares, Damage Progression, and Increased Cardiovascular disease in PaTients with SLE (PREDICTS) atherosclerosis-risk panel, which includes proinflammatory HDL (piHDL), leptin, soluble tumour necrosis factor-like weak inducer of apoptosis (sTWEAK) and homocysteine, as well as age and diabetes. A high PREDICTS score confers 28-fold increased odds for future atherosclerosis in SLE. The aim of this study is to determine whether PREDICTS biomarkers are modifiable by common lupus therapies. Methods: This prospective observational study included SLE subjects started on new lupus treatments. Leptin, sTWEAK, homocysteine and antioxidant function of HDL were measured at baseline (prior to drug initiation), 6 weeks and 12 weeks. Results: 16 subjects started mycophenolate (MMF), 18 azathioprine (AZA) and 25 hydroxychloroquine (HCQ). In MMF-treated subjects, HDL function progressively improved from 2.23 ± 1.32 at baseline to 1.37±0.81 at 6 weeks (p=0.02) and 0.93±0.54 at 12 weeks (p=0.009). sTWEAK levels also improved in MMF-treated subjects from 477.5±447.1 to 290.3±204.6 pg/mL after 12 weeks (p=0.04), but leptin and homocysteine levels were not significantly changed. In HCQ-treated subjects, only HDL function improved from 1.80±1.29 at baseline to 1.03±0.74 after 12 weeks (p=0.05). There were no changes in the AZA group. MMF treatment was still associated with significant improvements in HDL function after accounting for potential confounders such as total prednisone dose and changes in disease activity. Overall, the mean number of high-risk PREDICTS biomarkers at week 12 significantly decreased in the entire group of patients started on a new lupus therapy (2.1±0.9 to 1.8±0.9, p=0.02) and in the MMF-treated group (2.4±0.8 vs 1.8±0.9, p=0.003), but not in the AZA or HCQ groups. In multivariate analysis, the odds of having a high PREDICTS atherosclerosis risk score at 12 weeks were lower with MMF treatment (OR 0.002, 95% CI 0.000 to 0.55, p=0.03). Conclusions: 12 weeks of MMF therapy improves the overall PREDICTS atherosclerosis biomarker profile. Further studies will determine whether biomarker changes reflect decreases in future cardiovascular events.